Ultrasonically Aided Cross-Flow Membrane Filtration System For Latex Wastewater - Che Lah, Nuur Fahanis (2012)
In this current study, an ultrasonically-aided membrane filtration system that offers cleaned membrane after being fouled by latex wastewater was developed. Characterizations of latex wastewater were investigated to decide the best and suitable membrane used for this filtration system under optimum condition. Some characterization steps were done such as the latex particle size analysis, by using Transmission Electron Microscopy (TEM) and Atomic Force Microscope (AFM), pH, total solid (TS), total suspended solid (TSS), Biological Oxygen Demand (BODs), Chemical Oxygen Demand (COD) and viscosity. In order to obtain high permeability of the membrane, cellulose acetate membrane was used as the filter after characterized the latex wastewater based on the hydrophilicity of the membrane. Based on the literature, an ultrasonic-aided membrane filtration system was set up. The result from surface contact angle analysis proves that the membrane was a good hydrophilic membrane which is one of the crucial characteristic of a membrane used in this study. Fourier Transform Infra Red (FTIR) analysis was done to investigate the cleaning effectiveness of ultrasound waves to the fouled-membrane surface. The model of the fouling process was determined from the permeate flux trends.